Advances and challenges of public policies related to women's health in Brazil in the last 20 years: a literature review (Research, Society and Development, 2023)
Public policies needed to be revised and expanded to offer comprehensive care to women's health, given that gender is a social, dynamic, relational construction and that women do not make up a homogeneous group, thus, the consideration of factors that impact access in different ways to health is essential for this analysis. This article aims to address the advances and challenges, in the last 20 years, of public policies related to women's health in Brazil. For this, an integrative exploratory literature review was carried out. The PICO strategy (Patient, Intervention, Comparison and Outcome) was used to define the guiding question of the study. A bibliographical survey of articles, published between 2017-2022, that addressed the research theme was carried out. The discussion of public policies related to women's health requires understanding the Social Theory of Gender and how social structures of power influence health and illness processes. Despite the creation of specific laws, there is a lack of dialogue about inequalities and little participation of women in decision-making political spaces, which causes obstacles. In twenty years, even with recognized advances in relation to public policies dedicated to women in Brazil, there is still a long way to go in confronting inequalities to fully contemplate such a diverse population throughout its life cycle.